What Is the Next Generation of Transcatheter Mitral Valve Repair Devices? - Chen, Mi; Sun, Lizhong (Frontiers in Cardiovascular Medicine, 2021)
In the evolving scenario of the transcatheter mitral valve repair (TMVr), TMVr devices constitute a rapidly expanding field. The standard classification includes edge-to-edge repair, direct annuloplasty, indirect annuloplasty, chordal/papillary muscular repair, and the others. However, the unknowns and uncertainties to innovate a high-performing device are addressed. In this viewpoint, the authors discuss the potential future of the next generation and the challenges of TMVr devices.